2023
DOI: 10.1002/hsr2.1416
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes is associated with increased risk of death in COVID‐19 hospitalizations in Mexico 2020: A retrospective cohort study

Abstract: Background and Aim The COVID‐19 disease course can be thought of as a function of prior risk factors consisting of comorbidities and outcomes. Survival analysis data for diabetic patients with COVID‐19 from an up to date and representative sample can increase efficiency in resource allocation. The study aimed to quantify mortality in Mexico for individuals with diabetes in the setting of COVID‐19 hospitalization. Methods This retrospective cohort study utilized publicly available data from the Mexican Federal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Another comorbid that influences the survival rate of COVID-19 patients is diabetes mellitus, in line with the study results showing that the survival rate of patients without comorbidities is better than that of patients with DM from an analysis that is adjusted for the characteristics of respondents. This research supports previous research that COVID-19 patients with comorbid DM show an increase in severity (Sharif et al, 2021;Souza et al, 2022) and mortality rates (Huang & Huang, 2023;Yan et al, 2020). A meta-analysis study reported that the mortality rate and severity increased twofold in COVID-19 patients with DM compared to non-DM patients (Kumar et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Another comorbid that influences the survival rate of COVID-19 patients is diabetes mellitus, in line with the study results showing that the survival rate of patients without comorbidities is better than that of patients with DM from an analysis that is adjusted for the characteristics of respondents. This research supports previous research that COVID-19 patients with comorbid DM show an increase in severity (Sharif et al, 2021;Souza et al, 2022) and mortality rates (Huang & Huang, 2023;Yan et al, 2020). A meta-analysis study reported that the mortality rate and severity increased twofold in COVID-19 patients with DM compared to non-DM patients (Kumar et al, 2020).…”
Section: Discussionsupporting
confidence: 90%